Dengue Shock Syndrome: Its Similarity with Anaphylaxis and with the Homeopathic Medicine Apis mellifica (European Honeybee) - Richardson-Boedler, Cornelia (Homeopathy, 2021)
Dengue, with four viral serotypes, causes epidemics in tropical and sub-tropical regions. Allopathic antiviral therapies and a vaccine of general use are lacking. The homeopathic medicine Apis mellifica, advised in anaphylaxis from honeybee sting, is proposed to address the life-threatening dengue shock syndrome, which develops from dengue hemorrhagic fever and has features of anaphylaxis. In both dengue and anaphylaxis, immunoglobulin E activates, and released vasoactive mediators (importantly histamine, tryptase and platelet-activating factor) cause, a vascular permeability enabling shock. In dengue, another mechanism, namely antibody-dependent enhancement, due to secondary infection with a heterologous dengue serotype, is associated with release of vasoactive mediators. The homeopathic medicine Apis mellifica indicates plasma leak, shock, and the serous effusion that is noted in dengue patients, and is a suggested prophylactic and therapeutic medicine for dengue shock syndrome.
Keywords: dengue shock syndrome; anaphylaxis; homeopathy; Apis mellifica